Effects of comorbid alexithymia on cognitive impairment in chronic schizophrenia: a large-sample study on the Han Chinese population - Liao, Yuanping; Zhong, Yunhui; Yang, Kan; Zhang, Xiang-Yang (Frontiers in Psychiatry, 2025)
BackgroundAlexithymia and cognitive dysfunction are common in patients with schizophrenia. However, only a few studies have investigated the cognitive performance of patients with schizophrenia and comorbid alexithymia. This study aimed to investigate the relationship between alexithymia and neurocognitive impairment in patients with schizophrenia.MethodsA total of 695 patients who met the DSM-IV diagnostic criteria for schizophrenia were included in this cross-sectional study (male/female = 464/231). Demographic and clinical data were collected using self-reported questionnaires. The severity of alexithymia was assessed using the Toronto Alexithymia Scale (TAS-20), cognitive function was assessed using the Repeatable Battery for the Assessment of Neuropsychological Status (RBANS) tool, and the severity of psychiatric symptoms was assessed using the Positive and Negative Syndrome Scale (PANSS).ResultsThe prevalence of comorbid alexithymia in patients with chronic schizophrenia was 31.40%, with a male preponderance. Patients with alexithymia had higher PANSS negative symptom subscale scores and PANSS total scores than those without alexithymia (p < 0.05 for all). In addition, patients with alexithymia had more severe deficits in immediate memory, delayed memory, and language and lower RBANS scores than those without alexithymia. Stepwise multivariate regression analysis showed that alexithymia was a risk factor for language deficits and indicated low total RBANS scores in patients with schizophrenia.ConclusionThis study suggests that patients with chronic schizophrenia with alexithymia have poorer cognitive function than those without alexithymia. Some demographic characteristics and alexithymia are risk factors for cognitive dysfunction in patients with chronic schizophrenia.